AKSESBILITAS AIR BERSIH SEBAGAI HAK ASASI MANUSIA DALAM BIDANG LINGKUNGAN HIDUP DAN IMPLEMENTASINYA DI SEKOLAH DASAR - Nafsiatun Nafsiatun; Ari Widiyantoro; Kamarullah Kamarullah (VOX EDUKASI: Jurnal Ilmiah Ilmu Pendidikan, 2026)
Accessibility to clean water is a human right that must be fulfilled in everyday life. The ever-increasing human population results in increasing demands for clothing, food, shelter, clean water, and energy. This condition leads to excessive exploitation of natural resources that neglect the environment. Article 3 paragraph 3 of the 1945 Constitution of Republic of Indonesia that the earth, water, and natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. This rule serves as the basis for water resource management in Indonesia. This study aims to analyze accessibility to clean water as a human right in the environmental field and its implementation in elementary schools in three districts in West Kalimantan Province. The research methods included surveys, observations, and interviews in the schools that were the objects of the study. The data were then analyzed and compared with literature on the same theme. The results showed that 100% of schools have implemented the fulfillment of human rights in the form of clean water accessibility, but only 80% of supporting infrastructure is properly maintained. The implementation of human right and environmental understanding has been implemented in 3 subjects, namely IPAS, Bahasa Indonesia, and PPKN.